Surface-coated cutting tool

CN117062684BActive Publication Date: 2026-10-30MITSUBISHI MATERIALS CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202180096305.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-03-30
Publication Date
2026-10-30
Estimated Expiration
2041-03-30

AI Technical Summary

Benefits of technology

[0013]本发明是鉴于上述情况和上述方案而完成的,其目的是提供一种表面包覆切削工具,其即使提供于例如钛合金、镍合金等的热传导率低且韧性高的材料的高速切削,也呈现出优异的耐熔敷性、耐崩刀性,在长期使用中发挥优异的切削性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117062684B_ABST
    Figure CN117062684B_ABST
Patent Text Reader

Abstract

A surface-coated cutting tool comprises a tool substrate and a coating layer on the surface of the tool substrate. The tool substrate is composed of a WC-based cemented carbide with WC particles as the hard phase and Co as the binding phase. The tool is characterized in that: (a) an interface layer exists between the tool substrate and the coating layer; and (b) when regions A directly above the hard phase of the tool substrate and regions B directly above the binding phase of the tool substrate are defined in the interface layer, at a position where the average thickness of the interface layer is 1 / 2, the W content in region A is W... A It contains 90-99% by mass and has a C content of C. A The region B contains a proportion W. B It contains 30-65% by mass and has a C content of C. B And C A ≤0.05% by mass, C A ≤C B ≤0.09% by mass.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to surface-coated cutting tools (hereinafter, sometimes referred to as coating tools). Background Technology

[0002] As covering tools, there are inserts that can be freely mounted on the tip of a cutting tool in turning or planing of various steel or cast iron workpieces, drills or micro drills used in hole cutting of workpieces, and solid end mills used in planing, grooving or step cutting of workpieces. In addition, insert-type end mills that can be freely mounted on inserts and are used in the same cutting process as solid end mills are also known.

[0003] Furthermore, as coated tools, there are known tools that use WC-based cemented carbide as the tool matrix and form a coating layer on its surface. Various solutions have been proposed with the aim of improving cutting performance by focusing on the tightness of the interface between the tool matrix and the coating layer (film).

[0004] For example, Patent Document 1 discloses a coated tool with a TiAlN layer, which is formed by etching the tool substrate surface with Cr ions and / or Mo ions, and the coated tool has fewer Cr ion and / or Mo ion particles.

[0005] Additionally, for example, Patent Document 2 discloses a coating tool characterized by having a film on the surface of a WC-based cemented carbide substrate via a modified phase having a bcc structure, wherein the modified phase, apart from unavoidable impurities, has a metallic composition represented by the following general formula:

[0006] W 100-x-y M x Co y

[0007] [Where M is at least one element selected from Cr, V, Ni, Fe and Mn, Cr is an essential element and constitutes more than 70% by mass of the total M element, and (100-xy), x and y represent the contents (by mass%) of W, M and Co, respectively, satisfying the conditions 80≤100-xy≤95, 5≤x≤20 and 0.1≤y≤3], indicating that the modified phase is formed by ion bombardment treatment. This coating tool improves the adhesion of the film and can be used for cutting high-hardness steel, stainless steel, cast steel, etc.

[0008] Furthermore, for example, patent documents 3 and 4 propose a coating tool having a tool substrate and an intermediate film disposed on the tool substrate. The crystal structure of WC is indexed by a nanobeam diffraction pattern, and the film thickness, composed of carbides containing W and Cr, is 1 nm or more and 10 nm or less. This intermediate film improves the adhesion between the coating layer and the tool substrate, thereby increasing the tool life during machining of steel, cast iron, or heat-resistant alloys.

[0009] Patent Document 1: Japanese Patent Publication No. Hei 9-217168

[0010] Patent Document 2: Japanese Patent Publication No. 2014-152345

[0011] Patent Document 3: Japanese Patent Publication No. 2016-64487

[0012] Patent Document 4: Japanese Patent No. 6385233 Summary of the Invention

[0013] The present invention was made in view of the above circumstances and the above solution, and its object is to provide a surface-coated cutting tool that exhibits excellent resistance to melting and chipping, even when used for high-speed cutting of materials with low thermal conductivity and high toughness, such as titanium alloys and nickel alloys, and performs excellent cutting performance in long-term use.

[0014] Regarding the surface-coated cutting tools involved in the embodiments of the present invention.

[0015] The tool has a tool substrate and a coating layer on its surface. The tool substrate is composed of a WC-based cemented carbide with WC particles as the hard phase and Co as the binding phase.

[0016] (a) An interface layer exists between the tool substrate and the covering layer.

[0017] (b) When, in the interface layer, region A directly above the hard phase component constituting the tool matrix and region B directly above the bonding phase constituting the tool matrix are defined,

[0018] At a location where the average thickness of the interface layer is 1 / 2,

[0019] The region A contains a proportion of W. A It contains 90-99% by mass and has a C content of C. A ,

[0020] The region B contains a proportion of W. B It contains 30-65% by mass and has a C content of C. B,

[0021] And C A ≤0.05% by mass

[0022] C A ≤C B ≤0.09% by mass.

[0023] Furthermore, the surface-coating cutting tool involved in the above embodiments can satisfy the following (1).

[0024] (1) The region A further contains 1 to 10% by mass of Cr, and the region B further contains 30 to 60% by mass of Co and 5 to 10% by mass of Cr.

[0025] As mentioned above, even when used for high-speed cutting of difficult-to-cut materials such as titanium alloys and nickel alloys, the coating layer (film layer) has excellent resistance to melting and chipping, and exhibits excellent cutting performance in long-term use. Attached Figure Description

[0026] Figure 1 This is an example of a schematic diagram showing the tool substrate and the interface layer in a cross section (longitudinal section) perpendicular to the tool substrate surface of the surface-coated cutting tool according to an embodiment of the present invention. Detailed Implementation

[0027] In recent years, there has been a demand for versatile cutting tools that can handle high-speed and high-efficiency cutting processes and can process workpieces of as many material types as possible.

[0028] Based on the inventor's research, it has been determined that the conventional coated tools disclosed in Patent Documents 1-4 do not present particular problems when used for machining under normal cutting conditions such as steel or cast iron. However, when used for high-speed machining of difficult-to-machine materials such as Ti alloys and Ni alloys, the coating layer is prone to peeling due to the repeated formation and peeling of workpiece deposits on the cutting edge, and wear is also accelerated. That is, the following matters 1) and 2) are recognized.

[0029] 1) In the coated tool described in Patent Document 1, the etching treatment on the surface of the tool substrate is intended to prevent the increase of surface roughness by reducing the particles, rather than to prevent the peeling of the coating layer.

[0030] 2) The modified phase and intermediate film described in patent documents 2 to 4 are designed to improve the adhesion between the tool substrate (hard substrate) and the coating layer, but they do not consider application in high-speed cutting of difficult-to-cut materials such as Ti alloys and Ni alloys.

[0031] Therefore, in order to develop coated tools that exhibit excellent peel resistance, especially under high-speed machining of difficult-to-cut materials such as Ti alloys and Ni alloys, and excellent wear resistance during long-term use, the inventors have conducted in-depth research.

[0032] That is, it was found that when the tool matrix is ​​WC-based cemented carbide, the required close contact between the coating layer and the hard phase (WC particles) is different from the close contact between the coating layer and the bonding phase. The interface layer between the coating layer and the tool matrix was repeatedly studied.

[0033] The results yielded the following new insights.

[0034] 1) If the carbon content in the interface layer is significantly reduced, the adhesion between the tool substrate and the coating layer will be improved. Even in high-speed machining of difficult-to-machine materials such as Ti alloys and Ni alloys, the coating layer will not peel off, resulting in coated tools with satisfactory service life.

[0035] 2) At this point, the proportion of C is more preferably such that the portion of the tool matrix surface that is in contact with the hard phase (WC particles) is less than the portion that is in contact with the bonding phase.

[0036] Furthermore, it was found that these C-containing interface layers with different proportions could be obtained by controlling the bombardment of the tool matrix with metal ions under specific conditions.

[0037] The surface-coating cutting tool according to embodiments of the present invention will now be described in more detail. Furthermore, in this specification and claims, when a numerical range is expressed as "X~Y", the numerical range includes both an upper limit (Y) and a lower limit (X). Additionally, the units of the upper limit (Y) and the lower limit (X) are the same. Furthermore, the numerical values ​​have tolerances.

[0038] 1. Tool base:

[0039] The tool matrix of the surface-coated cutting tool involved in the embodiments of the present invention can be used as long as it contains WC particles as the hard phase component and Co is the main component of the bonding phase, without any particular restrictions.

[0040] Here, the reason for referring to the bonding phase as "mainly composed of Co" is that components such as TiC, VC, TaC, NbC, and Cr3C2, which are contained in the WC-based cemented carbide by being dispersed in or dissolved in the bonding phase, can also be included in the WC-based cemented carbide used in the tool matrix of the present invention.

[0041] Furthermore, the W content in the WC-based cemented carbide is preferably 85 to 95% by mass, and the content of Co, the main component of the bonding phase, is preferably 4 to 14% by mass.

[0042] 2. Interface layer

[0043] The surface-coated cutting tool of the present invention preferably has an interface layer between the tool substrate and the coating layer.

[0044] (1) Composition of regions in the interface layer

[0045] The interface layer has region A directly above the hard phase component (WC particles) that constitutes the tool matrix and region B directly above the binding phase that constitutes the tool matrix.

[0046] Here, region A directly above the hard phase component (WC particles) constituting the tool matrix refers to the region where the portion of the interface layer on the surface of the tool matrix that is in contact with the hard phase component (WC particles) extends in its thickness direction to the uppermost part of the interface layer (the interface in contact with the coating layer).

[0047] In addition, region B directly above the bonding phase constituting the tool matrix refers to the region where the portion of the interface layer on the surface of the tool matrix that is in contact with the bonding phase is extended in its thickness direction to the uppermost part of the interface layer (the interface in contact with the coating layer).

[0048] also, Figure 1 The schematic diagram illustrates the positional relationship between regions A5 and B6 of the aforementioned tool substrate 1 and interface layer 4. 2 represents the bonding phase, and 3 represents WC particles. Furthermore, in... Figure 1 The illustration of the covering layer is omitted in the image.

[0049] (2) Composition

[0050] The region A, located at 1 / 2 the average thickness of the interface layer, contains a proportion W of W. A Preferably, it is 90-99% by mass; on the other hand, the W content in region B at this location is W. B Preferably, it is 30-65% by mass.

[0051] Furthermore, the proportion of C in region A at that location is set as C. A The proportion of region B containing C is set as C. B hour,

[0052] Preferred C A ≤0.05% by mass

[0053] C A ≤C B ≤0.09% by mass.

[0054] Here, C A and C B The lower limit can be less than the analytical limit; in this case, it is treated as C. A =C B .

[0055] Furthermore, as described later, when using Cr ions for ion bombardment treatment to form the interface layer, the Cr content is more preferably 1 to 10% by mass in region A and more preferably 5 to 10% by mass in region B.

[0056] Furthermore, also in region B, it is more preferable to contain 30 to 60% by mass of Co.

[0057] Next, the reasons for preferably setting the content ratios of C, W, Co, and Cr within the aforementioned ranges in regions A and B will be explained. Furthermore, the location where the average thickness of the interface layer is 1 / 2 refers to a location independently determined in each of the multiple regions A and multiple regions B; the locations in regions A and B are not necessarily the same.

[0058] (2-1) Region A

[0059] Regarding the proportion of W... A The reason for favoring the above range is that when it is less than 90% by mass, the adhesion between the hard phase component (WC particles) in region A and the interface layer is insufficient; when it is greater than 99% by mass, the W in the tool matrix will decrease, and the porosity (void) in the tool matrix will increase, thereby reducing the wear resistance and toughness of the tool matrix itself. A More preferably, it is 93-96% by mass.

[0060] In addition, to improve the adhesion between the hard phase component (WC particles) in region A and the interface layer, C contains a proportion of C A Preferably, the content of C is less, with the upper limit preferably being 0.05% by mass and being the C content ratio in region B. B The lower limit can be less than the analytical limit (i.e., it can be completely free of C).

[0061] Furthermore, if the Cr content is within the above range, the adhesion between the coating layer and the interface layer will be further improved, making it less likely for the tool substrate surface to become embrittled. The Cr content is more preferably 3-7% by mass.

[0062] (2-2) Region B

[0063] Regarding the proportion of W... B The reason for favoring the above range is that when it is less than 30% by mass, the adhesion between the bonding phase in region B and the interface layer is insufficient; when it is greater than 65% by mass, the W in the tool matrix will decrease, and the porosity (void) in the tool matrix will increase, thereby reducing the wear resistance and toughness of the tool matrix itself. B More preferably, it is 40-60% by mass.

[0064] Additionally, if C contains a proportion of C BIf the content is greater than 0.09% by mass, the reduction in carbon on the tool matrix surface will be greater, forming embrittlement regions on the tool matrix surface. In addition, the lower limit of the carbon content can be less than the analytical limit (i.e., it can be completely free of carbon).

[0065] Furthermore, if the Cr content is within the above range, the adhesion between the coating layer and the interface layer will be further improved, making it less likely for the tool substrate surface to become embrittled. The Cr content is more preferably 6-9% by mass.

[0066] Furthermore, if the Co content is within the above range, the adhesion between the bonded phase and the interface layer will be further improved, the Co content in the tool matrix will not decrease, and the tool matrix's resistance to chipping and breakage will not decrease.

[0067] Furthermore, even if the surface-coated cutting tools according to the embodiments of the present invention are used for high-speed cutting of difficult-to-cut materials such as titanium alloys and nickel alloys, the reason why the coating has excellent resistance to melting and chipping and exhibits excellent cutting performance in long-term use is not yet clear. However, it is speculated that this is because Cr exists in the form of WCr in the interface layer and the two phases W and WCr are independent, and the proportion of C is small, so there are almost no carbides, which improves the toughness of the coating.

[0068] (3) Average layer thickness

[0069] The average thickness of the interface layer is preferably 1 to 500 nm. This is because when the average thickness is less than 1 nm, the adhesion between the tool substrate surface and the coating layer is not sufficiently improved due to the presence of the interface layer. On the other hand, when the average thickness is greater than 500 nm, the coating layer is easily peeled off due to the embrittlement of the tool substrate surface during the formation of the interface layer. The average thickness is more preferably 1 to 250 nm, and even more preferably 5 to 50 nm.

[0070] (4) Measurement method

[0071] Next, the composition of the interface layer and the method for measuring the average layer thickness will be explained.

[0072] (4-1) Composition of region A directly above the hard phase component (WC particles) that constitutes the tool matrix

[0073] Regarding the composition of region A, line analysis (TEM-EDS line analysis) was performed using an energy-dispersive X-ray spectrometer attached to a transmission electron microscope along a length of at least 550 nm from the coating layer directly above the hard phase component (WC particles) toward the interior of the tool substrate in a cross section (thickness direction) perpendicular to the tool substrate surface.

[0074] Since the coating layer is a nitride layer as described later, the point where no N was detected was taken as the end of the tool surface side of the interface layer, and the point where only W and C were detected simultaneously was taken as the end of the tool substrate side of the interface layer. The content ratio of W, Cr and C at the midpoint (1 / 2 position) of these two ends was measured.

[0075] Then, the line analysis was performed at at least five sites directly above the hard phase component (WC particles), and the average of their measurements was taken as the composition of region A.

[0076] In addition, the longitudinal section refers to the section perpendicular to the surface of the tool body when the minor unevenness of the tool body surface is ignored and it is treated as a flat surface in the case of cutting blades, etc., or the section perpendicular to the axis in shaft-type tools such as drill bits.

[0077] (4-2) Composition of region B directly above the bonding phase constituting the tool matrix

[0078] Regarding the composition of region B, TEM-EDS line analysis was performed in the longitudinal section along a measurement length of at least 550 nm from the coating layer directly above the bound phase component toward the interior of the tool matrix. Points where N was not detected were designated as the tool surface side end of the interface layer, while points where Co was detected but W was not detected were designated as the tool matrix side end of the interface layer. The content ratios of W, Cr, C, and Co at the midpoint (1 / 2 position) between these two ends were measured.

[0079] Then, the line analysis was performed at at least five sites directly above the bound phase, and the average of their measurements was taken as the composition of region B.

[0080] Furthermore, when determining the composition of region A and region B, if a line analysis result is obtained indicating the presence of only the metal (e.g., Cr) used in the bombardment process, the result of this line analysis is not used because of the particles that generate the metal, and a new line analysis is performed instead.

[0081] (4-3) Average layer thickness

[0082] As mentioned earlier, the average layer thickness is obtained by averaging the distances between the tool surface end and the tool substrate end at five locations in regions A and B respectively.

[0083] (5) Manufacturing method

[0084] The interface layer can be formed by bombardment with metal ions. For example, Cr, which is difficult to form particles, can be used as the metal ion. Besides Cr, Mo, which is also difficult to form particles, and Ti, which is frequently used in bombardment, can also be used. By using a metal that is difficult to form particles, the tool substrate surface becomes smooth, resulting in improved lifespan of the surface-coated cutting tool. In the bombardment process, it is preferable to set the processing temperature to a higher than usual temperature.

[0085] Here, although the reason for generating regions A and B with different compositions through bombardment is not yet clear, it is speculated that this may be because the high temperature of the bombardment or the introduction of gases such as Ar during bombardment ionizes the gas, which increases the amount of ion irradiation on the tool substrate surface, thereby promoting the diffusion and reaction of selective atoms due to the different compositions.

[0086] 3. Coating layer

[0087] As long as the coating layer is a composite nitride layer including a metal, conventionally known coating layers can be used without hindering the achievement of the aforementioned objectives. Examples include composite nitrides of Ti and Al, composite nitrides of Ti, Al and Cr, composite nitrides of Ti, Al and Si, and composite nitrides of Al and Cr.

[0088] The average thickness of the coating layer is preferably 0.5 to 10.0 μm. This is because when the average thickness is less than 0.5 μm, it cannot exhibit excellent wear resistance during long-term use, and the tool life will be shortened. On the other hand, when the average thickness is greater than 10 μm, abnormal damage such as chipping and breakage may occur.

[0089] In addition, the average layer thickness is obtained by magnifying the longitudinal section to an appropriate ratio (e.g., 5000 times), calculating the layer thickness at five points, and taking the average value.

[0090] The coating layer can be formed using either the conventional PVD or CVD method. If PVD is used, an arc ion plating apparatus (AIP apparatus) is preferred.

[0091] Example

[0092] Next, the embodiments will be described.

[0093] Here, as an embodiment of the coating tool of the present invention, a coating tool applied to a cutting tool is described, but the tool base can include WC as described above. The same applies to the case where the tool is applied to drills, end mills, etc. Furthermore, the coating layer is not limited to (Ti) (1-x-y) Al x M yN, 0.35≤x≤0.80, 0.00≤y≤0.15 (where x and y are atomic ratios, and M is an element in groups 4 to 6 of the IUPAC periodic table and at least one of Ce, La, Hf, and Nd).

[0094] First, as raw material powders, Co powder, VC powder, Cr3C2 powder, TiC powder, TaC powder, NbC powder, and WC powder were prepared. These raw material powders were combined into the composition shown in Table 1. Wax was further added and wet-mixed in a ball mill for 72 hours. After vacuum drying, the mixture was pressed into shape at a pressure of 100 MPa. These pressed bodies were sintered and processed into specified dimensions to produce tool bodies 1 to 3 made of WC-based cemented carbide with the blade shape of ISO standard SEEN1203AFTN1.

[0095] Next, after ultrasonically cleaning and drying the tool substrates 1 to 3 in acetone, they are mounted along their outer periphery at a predetermined distance radially away from the central axis of the rotary table within the AIP device. Furthermore, as the cathode electrode (evaporation source), any one of a Cr target, a Ti target, and a Mo target is provided, and a Ti-Al-M alloy target for obtaining a film of a predetermined composition is also provided.

[0096] Next, the air in the film-forming device is vented and maintained for 10 minutes. -2 While maintaining a vacuum below Pa, the device is heated to 960–1100°C using a heater. As shown in Table 2, an inactive atmosphere of 0.1–2.0 Pa is set, and a DC bias voltage of -1000–-1600V is applied to the tool substrate rotating on the aforementioned rotary table. The tool substrate surface is then bombarded for 5–40 minutes using any one of Cr, Ti, and Mo ions.

[0097] Then, nitrogen gas with a partial pressure in the range of 1.0 to 5.0 Pa as shown in Table 2 was introduced for a specified time. Between the cathode electrode (evaporation source) and the anode electrode made of Ti-Al-M alloy target, a specified current in the range of 80 to 240 A as shown in Table 2 was flowed to generate an arc discharge, and the coating tools of the present invention shown in Table 3 (hereinafter referred to as "Examples") 1 to 9 were produced.

[0098] On the other hand, for comparison, using the same film-forming apparatus as described above, an interface layer was formed on the tool substrates 1 to 3 under the conditions shown in Table 2, and a coating layer was formed to produce the coated tools (hereinafter referred to as "comparative examples") 1 to 4 of the comparative examples shown in Table 4.

[0099] For Examples 1-9 and Comparative Examples 1-4, the average layer thickness and the composition of the interface layer were measured as described above, and the results are shown in Tables 3 and 4, respectively. The measured values ​​in Tables 3 and 4 are average values.

[0100] [Table 1]

[0101]

[0102] "-" indicates that it does not contain.

[0103] [Table 2]

[0104]

[0105]

[0106] [Table 4]

[0107]

[0108] Next, for Examples 1-9 and Comparative Examples 1-4, single-edge planar milling tests were performed using SE445R0506E cutting tools. High-speed cutting tests were conducted on nickel alloys and titanium alloys under the following cutting conditions.

[0109] Cutting condition A:

[0110] Workpiece: A 60mm wide × 200mm long block of Ni-based alloy with the following composition (by mass%): Ni-19%, Cr-18.5%, Fe-5.2%, Cd-5%, Ta-3%, Mo-0.9%, Ti-0.5%, Al-0.3%, Si-0.2%, Mn-0.05%, Cu-0.04%, C.

[0111] Cutting speed: 75 m / min.

[0112] Depth of cut: 1.1mm

[0113] Feed rate: 0.09 mm / tooth.

[0114] Under the above conditions, wet high-speed, high-feed cutting tests were conducted on Ni-based alloys (typical cutting speed and feed rate were 25–40 m / min and 0.08 mm / tooth). Cutting was performed to a cutting length (test cutting length) of 1.8 m, the flank wear width was measured, and the tool tip wear condition was observed.

[0115] The results of the cutting test are shown in Table 5.

[0116] Cutting condition B:

[0117] Workpiece: A block of material, 60 mm wide and 200 mm long, with Ti-6%Al-4%V by mass.

[0118] Cutting speed: 90 m / min.

[0119] Depth of cut: 1.1mm

[0120] Feed rate: 0.09 mm / tooth.

[0121] Under the above conditions, wet high-speed, high-feed cutting tests were conducted on Ti-based alloys (typical cutting speed and feed rate were 30–45 m / min and 0.08 mm / tooth). Cutting was performed to a cutting length (test cutting length) of 1.8 m, the flank wear width was measured, and the tool tip wear condition was observed.

[0122] The results of the cutting test are shown in Table 6.

[0123] [Table 5]

[0124]

[0125] * Indicates the cutting life (sec) of the tool before reaching the test cutting length.

[0126] [Table 6]

[0127]

[0128] * Indicates the cutting life (sec) of the tool before reaching the test cutting length.

[0129] According to the results in Tables 5 and 6, for Examples 1 to 9, no abnormal damage such as chipping or peeling will occur under any of the cutting conditions A and B, and the resistance to melt deposition and chipping is excellent.

[0130] In contrast, it is clear that, regarding Comparative Examples 1 to 4, under either cutting condition A or B, the tool life is reached in a short time due to the occurrence of tool breakage or the progression of flank wear.

[0131] The embodiments disclosed above are merely exemplary in all respects and are not restrictive. The scope of the invention is defined by the claims, not by the foregoing embodiments, and is intended to include all modifications in the same sense and scope as the claims.

[0132] Industrial availability

[0133] The surface-coated cutting tool of the present invention exhibits excellent resistance to melting and chipping, especially in high-speed cutting of titanium alloys, nickel alloys, etc., which are accompanied by high heat generation and apply a large load to the cutting edge, and maintains excellent cutting performance over a long period of time. Therefore, it can satisfactorily address the issues of high performance of cutting equipment, labor-saving and energy-saving cutting processes, and low cost.

[0134] Explanation of reference numerals in the attached figures

[0135] 1. Tool base

[0136] 2. Combining phase

[0137] 3 WC particles

[0138] 4 Interface Layer

[0139] Area A, 5

[0140] Area B, 6

Claims

1. A surface-coated cutting tool, comprising a tool substrate and a coating layer on the surface of the tool substrate, wherein the tool substrate is composed of a WC-based cemented carbide with WC particles as the hard phase and Co as the binding phase, characterized in that, (a) An interface layer exists between the tool substrate and the covering layer. (b) When, in the interface layer, region A directly above the hard phase component constituting the tool matrix and region B directly above the bonding phase constituting the tool matrix are defined, At a location where region A of the interface layer is half the average layer thickness, W contains a proportion of W. A It contains 90-99% by mass and has a C content of C. A , At a location where region B of the interface layer is at half the average layer thickness, W contains a proportion of W. B It is 30-65% by mass, and the proportion of C is C. B , And C A ≤0.05% by mass C A ≤C B ≤0.09% mass.

2. The surface-coated cutting tool according to claim 1, characterized in that, The region A contains 1 to 10% by mass of Cr at half the average layer thickness, and the region B contains 30 to 60% by mass of Co and 5 to 10% by mass of Cr at half the average layer thickness.

Citation Information

Patent Citations

  • Engine speed control device for internal combustion engine for air conditioner

    JP1988085233A

  • Coating method for metallic or ceramics substrate

    JP1997217168A

  • Hard film coated WC based hard alloy member and method for producing the same

    JP2014152345A

  • Coated cutting tool

    JP2016064487A

  • Surface-coated cutting tool

    WO2020184352A1